ANRIL and ANRASSF1 long noncoding RNAs are upregulated in gastric cancer. Issue 8 (4th March 2019) - Kangarlouei, Roghayeh; Irani, Shiva; Noormohammadi, Zahra; Memari, Fereidoon; Mirfakhraie, Reza
Abstract: Gastric cancer (GC) is the fifth most frequent cancer and the third‐leading cause of cancer‐related death worldwide. It is a highly heterogeneous disease regarding the morphological and molecular viewpoints. Since it is curable in primary stages, early detection could improve the survival rate. Long noncoding RNAs contribute to a variety of cellular mechanisms, and their dysregulation is reported in various diseases such as cancer. Thus, they have a great potential to be used as diagnostic and prognostic biomarkers and therapeutic targets as well. In the current study, ANRIL and ANRASSF1 expression levels were compared between GC tumors and the adjacent normal tissues collected from 39 Iranian patients using the quantitative real‐time polymerase chain reaction method. Correlation between ANRIL and ANRASSF1 expression levels and other clinical parameters was also evaluated. ANRIL and ANRASSF1 were significantly overexpressed in GC tumors compared with adjacent tissues ( P  < 0.0001 and P  = 0.001, respectively). No significant correlation between ANRIL and ANRASSF1 expression levels and demographic information was found. This study suggests that ANRIL and ANRASSF1 may play a critical role in GC progression and can be considered as a potential diagnostic or therapeutics biomarkers.